Effects of Starch Overload and Cecal Buffering on Fecal Microbiota of Horses - Bustamante, Caio C. [UNESP]; de Paula, Vanessa B. [UNESP]; Rabelo, Isabela P. [UNESP]; Fernandes, Camila C. [UNESP]; Kishi, Luciano T. [UNESP]; Canola, Paulo A. [UNESP]; Lemos, Eliana Gertrudes de M. [UNESP]; Valadão, Carlos Augusto A. [UNESP] (MDPI, 2022)
Starch overload in horses causes gastrointestinal and metabolic disorders that are associated with microbiota changes. Therefore, we identified the fecal microbiota and hypothesized that intracecal injection of alkaline solution (buffer; Mg(OH)2 + Al(OH)3) could stabilize these microbiota and clinical changes in horses submitted to corn starch overload. Ten crossbred horses (females and geldings) were allocated to group I (water–saline and starch–buffer treatments) and group II (water–buffer and starch–saline treatments). Clinical signs, gross analysis of the feces, and fecal microbiota were evaluated through 72 h (T0; T8; T12; T24; T48; T72). Corn starch or water were administrated by nasogastric tube at T0, and the buffer injected into the cecum at T8 in starch–buffer and water–buffer treatments. Starch overload reduced the richness (p < 0.001) and diversity (p = 0.001) of the fecal microbiota. However, the starch–buffer treatment showed greater increase in amylolytic bacteria (Bifidobacterium 0.0% to 5.6%; Lactobacillus 0.1% to 7.4%; p < 0.05) and decrease in fibrolytic bacteria (Lachnospiraceae 10.2% to 5.0%; Ruminococcaceae 11.7% to 4.2%; p < 0.05) than starch–saline treatment. Additionally, animals that received starch–buffer treatment showed more signs of abdominal discomfort and lameness associated with dysbiosis (amylolytic r > 0.5; fribolytic r < 0.1; p < 0.05), showing that cecal infusion of buffer did not prevent, but intensified intestinal disturbances and the risk of laminitis.
Keywords: dysbiosis; equine; feces; NSG; Ruminococcaceae; starch overload; Streptococcus